The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.ijinfomgt.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

How younger elderly realize usefulness of cognitive training video games to maintain their independent living

Abstract: The objective of this paper is to understand the perception that younger elderly persons have towards the usefulness of playing Xbox Kinect video games as an assistive technology that is designed to maintain their cognitive abilities. Available literature highlights two kinds of assistive technologies; the first being Supportive Technologies that provide aid for already-declined functional abilities (such as hearing aids), and the second being Empowering Technologies that maintain functional abilities which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
1
8
0
2
Order By: Relevance
“…The results demonstrate that this can be achieved in a number of ways, including rewards, achievements, and competitive play with family and friends. This has parallels with the findings of Talaei-Khoei and Daniel [ 12 ], who found that their participants were motivated to improve their memory age as they experienced with a sense of achievement and reward. This study also found that participants wanted an extra level of socialization within the app through a virtual competition with friends to share scores and achievements.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The results demonstrate that this can be achieved in a number of ways, including rewards, achievements, and competitive play with family and friends. This has parallels with the findings of Talaei-Khoei and Daniel [ 12 ], who found that their participants were motivated to improve their memory age as they experienced with a sense of achievement and reward. This study also found that participants wanted an extra level of socialization within the app through a virtual competition with friends to share scores and achievements.…”
Section: Discussionsupporting
confidence: 86%
“…The findings from this study demonstrate that even with this knowledge, changing health behaviors is challenging and often unsuccessful [ 16 ]. It is therefore critical to adopt the proposals of Talaei-Khoei and Daniel [ 12 ] and employ qualitative methods, as in this study, to focus specifically on why end users would find a training game to be useful and adopt it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, there has also been a growing body of research on the use of games to assess and train cognitive abilities in a variety of ways [38][39][40][41][42]. Specialized and standardized therapeutic applications of video gaming may help people with EF deficits to maintain cognitive functions [43].…”
Section: Discussionmentioning
confidence: 99%